2013
DOI: 10.1016/j.ijporl.2013.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Acute otitis media in infants younger than three months not vaccinated against Streptococcus pneumoniae

Abstract: S. pneumoniae is the most frequent pathogen to cause AOM in this age group. Empirical treatment with amoxicillin or ceftriaxone should be considered depending on clinical suspicion of severe invasive infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Resistance to fluoroquinolones has also been demonstrated 72,75. Similarly, nontypeable H. influenza e, the main serotype responsible for OM, frequently produces beta-lactamase, and is thus resistant to ampicillin;29,76,77 amoxicillin/clavulanate may be preferred,77 but a study in Spain found that 13% of the nontypeable H. influenza e isolates were even amoxicillin/clavulanate resistant 29…”
Section: Emerging Strategies In Prevention and Treatmentmentioning
confidence: 99%
“…Resistance to fluoroquinolones has also been demonstrated 72,75. Similarly, nontypeable H. influenza e, the main serotype responsible for OM, frequently produces beta-lactamase, and is thus resistant to ampicillin;29,76,77 amoxicillin/clavulanate may be preferred,77 but a study in Spain found that 13% of the nontypeable H. influenza e isolates were even amoxicillin/clavulanate resistant 29…”
Section: Emerging Strategies In Prevention and Treatmentmentioning
confidence: 99%
“…Compared to older children, infants who experience AOM before age 12 months are more likely to experience recurrent AOM, prolonged middle ear effusion, concomitant conductive hearing loss, and a greater likelihood of requiring tympanostomy tube surgery [2,4]. Also, very young infants may be susceptible to pneumococcal AOM because they may not have been fully immunized with pneumococcal vaccine [5]. Worldwide, parents consider the symptoms of AOM to be a burden [6].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, researchers have used the examination by otolaryngologists, who often use surgical microscopes and/or tympanocentesis results to support the clinical diagnosis of AOM. 3,4,6,7 However, these methods are not routinely used in current clinical practice. 19 Although examining the ears of young infants is technically challenging, previous researchers have demonstrated successful use of otoscopy to diagnose AOM in infants younger than 8 weeks, with 52% to 85% of middle ear effusion cultures yielding growth of true otopathogens after tympanocentesis.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, researchers have suggested a low prevalence of bacteremia among infants with AOM, but these studies were limited by small sample sizes and included mixed populations of infants with and without fever. [3][4][5][6][7][8] The clinical conundrum of AOM in infants younger than 3 months may be most relevant to those without fever, for whom the appropriate diagnostic evaluation for IBI, if any, is unclear.…”
mentioning
confidence: 99%